Elderly widows : socio-economic and demographic study in Jharkhand - Gupta, Sangeeta
Widows are the most neglected and vulnerable segment among the elderly population in India. They face deprivation in society on many counts-being women, poor, and widowed. Elderly widows face deprivation within their own families and within the village community. They are vulnerable to many difficulties, including economic hardships, lack of physical help, neglect, abuse, and social stigma. Based on a sample survey of 300 elderly widows from Jharkhand state, this study comprehensively examines the socio-cultural, economic, health, and psychological dimensions of widowhood for the elderly in a rural setting. This insightful study for the first time addresses the complex scenario of vulnerability and deprivation among elderly widows and raises important concerns for the attention of policy makers and those involved in the welfare of the aged and widows in India. Study conducted in East Singhbhum District, Jharkhand, India.